Analys av parathormon och joniserat kalcium i blod hos hund - Cegrell, Emma (SLU/Dept. of Animal Environment and Health (until 231231), 2004)
The calcium homeostasis in the body is normally strict regulated to be kept within very narrow limits. This regulation is due to the action of parathyroid hormone (PTH) which is synthesized in the chief cells of the parathyroid glands. In different diseases, the calcium homeostasis is disturbed and this could either be due to a dysfunction of the parathyroid gland itself, or it could have a completely different explanation. To investigate disturbed calciumhomeostasis, ionized calcium and PTH can be analyzed from a blood sample. There are a lot of different assays to measure PTH in humans. Some of these assays can also be used on dogs.